A new species of Merremia (Convolvulaceae) from São Paulo State, Brazil - Petrongari, Fernanda Satori; Simão-Bianchini, Rosângela (Phytotaxa, 2016)
Taxonomic studies of the genus Merremia from São Paulo State have resulted in the recognition of a new species endemic of “campo cerrado”: Merremia hoehnei, a prostrate subshrub which is distinguished by the presence of simple and 2–3-rayed stellate trichomes. This new species is described, illustrated and its similarities with related species (Merremia digitata, M. hassleriana, and M. hirsuta) are discussed.